Investigation of anti-nociceptive, anti-inflammatory potential and ADMET studies of pure compounds isolated from Isodon rugosus Wall. ex Benth - Alshehri, Osama M.; Zeb, Anwar; Mukarram Shah, Syed Muhammad; Mahnashi, Mater H.; Asiri, Saeed Ahmed; Alqahtani, Omaish; Sadiq, Abdul; Ibrar, Muhammad; Alshamrani, Saleh; Jan, Muhammad Saeed (Frontiers in Pharmacology, 2024)
The strong ethnopharmacological utilization of Isodon rugosus Wall. Ex. Benth is evident in the treatment of several types of pain and inflammation, including toothache, earache, abdominal pain, gastric pain, and generalized body pain and inflammation. Based on this background, the antinociceptive effects of the crude extract, various fractions, and essential oil have been reported previously. In this research work, we isolate and characterize pure bioactive compounds from I. rugosus and evaluate possible mechanisms using various in vivo and in vitro models. The pure compounds were analyzed for analgesic and anti-inflammatory activities through various assays. The column chromatography of the chloroform fraction of I. rugosus led to the identification of two pure compounds, i.e., 1 and 2. Compound 1 demonstrated notable inhibition (62% writhing inhibition, 72.77% COX-2 inhibition, and 76.97% 5-LOX inhibition) and anti-inflammatory potential (>50% paw edema inhibition at various intervals). The possible mechanism involved in antinociception was considered primarily, a concept that has already been elucidated through the application of naloxone (an antagonist of opioid receptors). The involvement of adrenergic receptors was investigated using a hot plate model (an adrenergic receptor antagonist). The strong ethnomedicinal analgesic background of I. rugosus, supported by previous reports and current observations, leads to the conclusion that I. rugosus is a potential source of antinociceptive and anti-inflammatory bioactive compounds. It may be concluded from the results that the isolated analgesic compounds of I. rugosus may be a possible alternative remedy for pain and inflammation management with admirable efficacy and safety profiles.